1993
DOI: 10.1111/j.1365-3040.1993.tb00874.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of enhanced ozone and enhanced carbon dioxide concentrations on biomass, pigments and antioxidative enzymes in spruce needles (Picea abies L.)

Abstract: During one growing period, 5‐year‐old spruce trees (Picea abies L., Karst.) were exposed in environmental chambers to elevated concentrations of carbon dioxide (750 cm3 m−3) and ozone (008 cm3 m−3) as single variables or in combination. Control concentrations of the gases were 350cm3 m−3CO2 and 0.02 cm3 m −3 ozone. To investigate whether an elevated CO2 concentration can prevent adverse ozone effects by reducing oxidative stress, the activities of the protective enzymes superoxide dismutase, catalase and perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
55
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 33 publications
10
55
2
Order By: Relevance
“…This implies that uptake and transfer of these nutrients into the current-year needles did not satisfy the demand generated by enhanced growth at elevated CO, (see Norby, O'Neill & Luxmore, 1986;Polle et al, 1993). However, care needs to be taken in the interpretation of these data because starch accumulated in the needles of CO2-enriched trees over the course of the season (Barnes et al, 1995a).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that uptake and transfer of these nutrients into the current-year needles did not satisfy the demand generated by enhanced growth at elevated CO, (see Norby, O'Neill & Luxmore, 1986;Polle et al, 1993). However, care needs to be taken in the interpretation of these data because starch accumulated in the needles of CO2-enriched trees over the course of the season (Barnes et al, 1995a).…”
Section: Discussionmentioning
confidence: 99%
“…The negative impact of O $ on  was related to increased leaf dark respiration, decreased photosynthesis and\or decreased . Kull et al (1996) Polle et al (1993) did not find that CO # enrichment protected against O $ stress by increasing protective enzymes. Ozone reduced growth in current-year shoots, whereas CO # prevented this.…”
Section: Interaction With Ozonementioning
confidence: 99%
“…In combination, ozone damage to photosynthetic tissues is ameliorated by elevated [CO # ], and recent studies have examined the mechanisms behind this interaction (Kramer et al, 1991 ;Polle et al, 1993 ;McKee et al, 1995McKee et al, , 1997bRao et al, 1995 ;Booker et al, 1997 ;Volin et al, 1998 ;Wieser et al, 1998). In controlled-environment studies, in which spring wheat was exposed to chronically elevated concentrations of CO # and\or O $ , the effect of elevated [O $ ] on photosynthesis resulted mainly from a loss of Rubisco activity (McKee et al, 1995(McKee et al, , 1997b.…”
Section: Concurrent Emissions Of Nitrogen Oxides and Volatile Organicmentioning
confidence: 99%
“…7) , 1997bFiscus et al, 1997) ; this protective effect, as shown in this study, might be less consistent under variable field conditions. Second, greater availability of photosynthate under elevated [CO # ] might enhance detoxification capacity (Rao et al, 1995), although some studies suggest that this may be of minor importance (Polle et al, 1993 ;McKee et al, 1997b $ -sensitive Rubisco limitation to the relatively insensitive RuBP-regeneration limitation. In this experiment, a compensatory shift in photosynthetic control was also observed in the flag leaf at noon on Day III (Fig.…”
mentioning
confidence: 99%